Imaging of an Indeterminate Pancreatic Mass - Anu Eapen; Anuradha Chandramohan; Reetu John; Betty Simon; Tharani Putta; A. J. Joseph (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Several conditions ranging from neoplasm to inflammatory disorders can present as a pancreatic mass on imaging. While classic imaging features help us make an accurate diagnosis, we are often confronted by indeterminate pancreatic masses that pose diagnostic dilemma. In this review, we describe the typical imaging features of common mass forming conditions of pancreas followed by description of atypical imaging appearances, which make a pancreatic mass indeterminate. We also emphasize on imaging features useful in differentiating one from the other.